Is the Influence of Oil Shocks on Economic Policy Uncertainty Fading? - Bahram Adrangi; Arjun Chatrath; Debasish Maitra; Anirban Sengupta (American Business Review)
Anecdotal evidence indicates that the influence of crude oil shocks on US economic performance and, by extension, economic policy uncertainty is in decline. While existing studies present mixed evidence on the relationship between economic policy uncertainty and structural oil shocks, they fail to assess any time variation in this relationship. We examine the temporal nature of the influence of three structural oil shocks, oil supply shocks, global aggregate demand shocks, and shocks due to oil market-specific demand, on categorical economic policy uncertainty indexes from 1986 to 2023. We find that out of three oil shocks, only oil market-specific demand shocks negatively and significantly affect the US policy uncertainty over high-uncertainty regimes, with monetary policy uncertainty being the most influenced. At the same time, the impact of the other two shocks, oil supply shocks and aggregate demand shocks on EPU, is found to be fading. The oil shocks-EPU relationship exhibits regime dependencies with higher impact during the high volatile regime. Also, the role of partisan conflict in influencing the oil shocks-EPU relationship is established specifically in EPU subcategories relating to government expenditures. Hence, this paper uncovers interesting dynamics of the oil shocks-EPU relationship, such as regime dependencies, time-varying relationship, the importance of partisan conflict, and the fading influence of global oil supply shocks and oil shocks due to aggregate demand in the global economy.